Le courtier d’assurance et l’assuré - Dalpé, Jean (Assurances)

(untitled) (HEC Montréal, 1982)
There exists a mutual interest between the broker and the insured which becomes evident when an insurance risk is placed or at the time a loss occurs. To illustrate this relationship, the author presents a number of cases in which services rendered by the broker to the client were high appreciable. Clients should indeed perceive insurance not simply as a good obtained, nor the best offer tendered, but rather a service the value of which one realizes when confronted with a loss.